Prevention of Thalassaemia by Genetic Counseling (Anwer Khan Modern Medical College Journal, 2011)
Thalassaemia is the most common inherited disorder in the world with a wide geographical variation in incidence. According to World Health Organization (WHO) at last 30% of Bangladesh population are carrions of Beta thalassaemia and 4.0% are carriers of Hb-E in Bangladesh. It is presumed that approximately 6000 thalassaemic children are born each year in Bangladesh. A recent study showed that carrier state of Hb-E is 6.1% and as high as 40% in Tribal children in Bangladesh. Early genetic, diagnosis, proper counseling, Health Education Community based prevention are necessary for the improvement of this inherited disorder in Bangladesh. Key Words: Thalassaemia; Bangladesh; Early Diagnosis; Counselings; Community Based Prevention; Health Education DOI: http://dx.doi.org/10.3329/akmmcj.v2i2.8169 AKMMC J 2011; 2(2): 26-28